Pemanfaatan Limbah dan Pengelolaan Lingkungan untuk Pertanian Berkelanjutan melalui Pembuatan Biopestisida Daun Bandotan dan Briket di Desa Pekan Sawah - Rina Maharany; Tifany Zia Aznur; Brefty Meysi Afrilia F; Reza Ade Nugraha; Sairul Hafiz Ikhwana; Anggun Riskananda Syahren; Tifany Aulia R Hasibuan; Asep Rahmat Hidayat (BADAN PENERBIT STIEPARI PRESS, 2025)
The use of inorganic pesticides to control pests and diseases in oil palm plants remains the primary choice for most farmers. However, the continuous use of chemical pesticides in large quantities can have negative impacts, both on human health and environmental sustainability. Based on these problems, a Community Service (PKM) program was conducted in Pekan Sawah Village, Sei Bingai District, Langkat Regency, which aims to empower the community through waste utilization and environmental management to achieve sustainable agriculture. The main activities of this program include the production of natural biopesticides based on bandotan leaves (Ageratum conyzoides), as well as the utilization of agricultural waste such as corn cobs and oil palm fronds into environmentally friendly briquettes. Through this activity, farmers are equipped with knowledge and practical skills to reduce dependence on chemical pesticides and fossil-based fuels. Thus, it is hoped that farmers will be able to reduce production costs, increase efficiency, and maintain health and environmental sustainability. The PKM activity was held on July 31, 2025, at the Pekan Sawah Village Office, with a total of 35 farmers participating. Throughout the program, community enthusiasm was evident. Farmers not only actively participated in the extension sessions but also demonstrated the biopesticide and briquette-making techniques taught. This demonstrated that the innovations introduced were easy to implement and relevant to their needs. The results demonstrated that the program not only provided practical solutions to reduce the impact of inorganic pesticide use but also increased farmer awareness of waste management. Furthermore, this PKM has the potential to improve community economic and social well-being, while simultaneously encouraging the creation of a more environmentally friendly and sustainable agricultural system.